2018
DOI: 10.1161/jaha.117.008181
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Short‐Term Calorie Restriction for Prevention of Acute Kidney Injury After Cardiac Surgery: A Randomized, Controlled, Open‐Label, Pilot Trial

Abstract: BackgroundAcute kidney injury is a frequent complication after cardiac surgery and is associated with adverse outcomes. Although short‐term calorie restriction (CR) has proven protective in rodent models of acute kidney injury, similar effects have not yet been demonstrated in humans.Methods and Results CR_KCH (Effect of a Preoperative Calorie Restriction on Renal Function After Cardiac Surgery) is a randomized controlled trial in patients scheduled for cardiac surgery. Patients were randomly assigned to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Recently, in a randomized controlled clinical trial evaluating the effects of a 7-day preoperative CR (60% of DEE) on renal function in patients undergoing cardiac surgery, a small albeit significant improvement on creatinine kinetics was revealed at 48 h after surgery and before discharge. 21 Similar to the here reported trial, more pronounced beneficial effects were detected in distinct patient subgroups. Despite these promising data, the magnitude of the observed effects is considerably lower than it could have been expected from animal experiments.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, in a randomized controlled clinical trial evaluating the effects of a 7-day preoperative CR (60% of DEE) on renal function in patients undergoing cardiac surgery, a small albeit significant improvement on creatinine kinetics was revealed at 48 h after surgery and before discharge. 21 Similar to the here reported trial, more pronounced beneficial effects were detected in distinct patient subgroups. Despite these promising data, the magnitude of the observed effects is considerably lower than it could have been expected from animal experiments.…”
Section: Discussionsupporting
confidence: 86%
“…To answer the question if CR-induced reduction of endocannabinoids and specifically AEA is even conserved in humans, we assembled a set of longitudinally acquired human serum samples before and after CR derived from different investigator initiated clinical trials at our center. The first trial investigated the protective effect of CR in patients undergoing elective cardiac surgery on cardiopulmonary bypass (CR_KCH, NCT01534364, [ 36 ]). After randomization, subjects received a formula diet that supplied 60% of daily energy expenditure (DEE) for the last seven days prior to surgery; control subjects were not restricted in their food intake.…”
Section: Resultsmentioning
confidence: 99%
“…Median weight loss in the control group was 0•1 kg, whereas median weight loss in the ER group was 3•0 kg. There was a trend towards lower incidence of AKI in the ER group (42•0 v. 47•5 %, P 0•06) (23) . These promising studies should be confirmed in larger trials.…”
Section: Human Studiesmentioning
confidence: 86%